(untitled) (Cadernos de Sociomuseologia, 2025)
Abstract: The journey from traumatic memories to museums is made up of diverse and complex stages, requiring a unique and sensitive approach, where methodological technique must be associated with a human awareness of ethics and empathy. Given this complexity, this article seeks to carry out a brief bibliographical review of concepts and reflections to understand how traumatic memories can be better collected, preserved and presented. Firstly, the approach is about the encounter between oral history and traumatic memories, detailing the issues that impact collective and social memory, as well as the concept of trauma and its reflections on memory. Afterwards, we reflect on the technical issue based on the concepts of oral memory collection in the methodological approaches of oral history, social sciences and journalism, as well as its association with sensitive listening. The final stage of the journey of traumatic memories to museums is precisely the meeting of this collected memory with the concepts of museology, especially Sociomuseology, where the essential commitments are with life and human rights. This stage also addresses a fundamental point in the process: the educational potential of traumatic memories within museum institutions. Finally, we conclude how all these concepts and reflections meet and complement each other in the purpose of collecting and preserving traumatic memories with technique, ethics and sensitivity. Keywords: oral history; social memory; traumatic memories; sociomuseology